Dysexecutive mild cognitive impairment associated to frontal atrophy: Case report - Balthazar,Marcio Luiz Figueredo (2008)
Abstract Non-amnestic mild cognitive impairment (MCI) evolving to neurodegenerative diseases other than Alzheimer's disease (AD) is rarely well documented. We report a case of a 49 year-old woman who presented a slowly progressive attentional/dysexecutive syndrome sparing other cognitive domains and without significant impairment of daily life activities. Her mother had Parkinsonism and her brother, a psychotic syndrome. Brain CT/MRI showed frontal atrophy while brain SPECT showed moderate cortical hypoperfusion, mainly in the frontal lobes. Our case is an example of non-memory MCI whose neuropsychological data and brain imaging indicating high likelihood of progression to a non-AD dementia.